1989
DOI: 10.1161/01.cir.79.2.281
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of intravenous tissue plasminogen activator and early intravenous heparin in acute myocardial infarction.

Abstract: To evaluate the coronary thrombolytic efficacy of tissue plasminogen activator (t-PA) and early intravenous heparin, 134 patients with acute myocardial infarction were randomly assigned to combination therapy or t-PA only. At a median of 2.78 hours from symptom onset, 64 patients received both t-PA (1.5 mg/kg/4 hr) and a bolus of 10,000 units heparin, whereas 70 patients received t-PA alone at the same dose. All patients underwent coronary angiography 90 minutes after initiation of therapy to determine infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(48 citation statements)
references
References 25 publications
1
45
0
2
Order By: Relevance
“…Although heparin has proven to be an extremely effective antithrombotic agent, both experimental and clinical studies indicate that it is limited in its ability to inhibit the propagation of venous thrombi (14)(15)(16)(17)(18) or to prevent coronary rethrombosis after thrombolytic therapy (19,20). The studies presented here provide a plausible explanation for these limitations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although heparin has proven to be an extremely effective antithrombotic agent, both experimental and clinical studies indicate that it is limited in its ability to inhibit the propagation of venous thrombi (14)(15)(16)(17)(18) or to prevent coronary rethrombosis after thrombolytic therapy (19,20). The studies presented here provide a plausible explanation for these limitations.…”
Section: Discussionmentioning
confidence: 88%
“…Heparin is an effective antithrombotic agent that acts primarily by catalyzing the inactivation of thrombin and activated Factor X by antithrombin III (8)(9)(10)(11) (19) or in man (20).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, several adjunctive therapies have been used with thrombolytic agents. Clinically, the use of aspirin, dipyridamole, calcium channel blockers, heparin, or nitrates have had little impact on the 20-30% acute rethrombosis rate with either streptokinase or rt-PA. [24][25][26] The model described in this study uses electrical induction of vessel wall injury as a means of promoting intracoronary artery thrombosis in the presence of a stenosis. The experimental models appears to mimic the clinical situation with respect to a spontaneously developing thrombus in response to endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…After review of abstracts, an additional 16 studies were excluded. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] After review of the full article, an additional 8 studies were excluded because they were not properly randomized (nϭ3) [33][34][35] ; because at least 1 randomized treatment group did not receive aspirin (nϭ3) 36 -38 ; or because they were preliminary reports or the results of a substudy with the main results having been reported elsewhere (nϭ2). 39,40 Clinical outcome data could not be obtained for 1 additional study, 41 leaving 14 randomized trials, involving a combined total of 25 280 patients, for inclusion in the meta-analysis (Tables 1 to 3).…”
Section: Study Selectionmentioning
confidence: 99%